2022
DOI: 10.1038/s41419-022-05299-2
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CRABP2 by TET1-mediated DNA hydroxymethylation attenuates mitochondrial apoptosis and promotes oxaliplatin resistance in gastric cancer

Abstract: Oxaliplatin is the main chemotherapy drug for gastric cancer (GC), but quite a few patients are resistant to oxaliplatin, which contributes to the poor prognosis of GC patients. There is therefore an urgent need to identify potential targets for reversing chemotherapy resistance in GC patients. In this study, we analyzed the tumor samples of GC patients who received neoadjuvant chemotherapy based on oxaliplatin through quantitative proteomics and identified the potential chemoresistance-related protein cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Furthermore, the positive correlation between CRABP2 and HIF1α protein expression in ovarian cancer tissues, particularly in chemotherapy-insensitive tumors, further supports the clinical relevance of this interaction. Interestingly, it has been reported that CRAPB2 accelerates ubiquitination-mediated BAX degradation in gastric cancer cells, thereby alleviating mitochondrial apoptosis and promoting oxaliplatin resistance [ 45 ]. Therefore, CRAPB2 may regulate the development of drug resistance in a variety of tumors through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the positive correlation between CRABP2 and HIF1α protein expression in ovarian cancer tissues, particularly in chemotherapy-insensitive tumors, further supports the clinical relevance of this interaction. Interestingly, it has been reported that CRAPB2 accelerates ubiquitination-mediated BAX degradation in gastric cancer cells, thereby alleviating mitochondrial apoptosis and promoting oxaliplatin resistance [ 45 ]. Therefore, CRAPB2 may regulate the development of drug resistance in a variety of tumors through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…CRABP2 was identified as a TMB-related gene in SKCM, and the significance of CRABP2 for tumor prognosis was attempted to analyze from two immune-related aspects: TMB and immune infiltration [ 33 ]. In STAD, CRABP2 was highly expressed under TET1-mediated DNA hydroxymethylation, which was correlated with poor OS and promoted oxaliplatin resistance [ 48 ]. There is currently no research focusing on the role of CRABP2 in TGCT.…”
Section: Discussionmentioning
confidence: 99%
“…57 Besides, enriched in the promoter region of CRABP2, TET1 can increase its expression, thereby inhibiting Bax-dependent apoptosis to induce oxaliplatin resistance in gastric cancer cells. 58 Interestingly, TET1 knockdown can cause lung cancer cells resistant to gefitinib. 59 Similarly, the knockdown of TET2 triggered resistance in BRCA2 deficient cells to multiple poly (ADP-ribose) polymerase (PARP) inhibitors and cisplatin.…”
Section: Dna Methylation and Drug Resistancementioning
confidence: 99%